2022
DOI: 10.1039/d1ma00954k
|View full text |Cite
|
Sign up to set email alerts
|

Simple non-fused small-molecule acceptors with bithiazole core: synthesis, crystallinity and photovoltaic properties

Abstract: Three simple-structure non-fused-ring SMAs with an Aw(π–A)2 architecture using bithiazole as the central unit was synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…89 The weak electron-deficient 4,4′-dimethyl-2,2′-bithiazole was used as the core unit to construct two acceptors BTz-4F-1 and BTz-4Cl-1. 90 When paired with J71, BTz-4F-1 and BTz-4Cl-1 based devices provided PCEs of 5.72% and 3.93%, respectively. Besides the 4T backbone, A3T-2 and A3T-5 with the terthiophene backbone were also designed and provided moderate PCEs of 6.20% and 7.03%, respectively.…”
Section: Nfas With Fully Non Fused Backbonesmentioning
confidence: 96%
“…89 The weak electron-deficient 4,4′-dimethyl-2,2′-bithiazole was used as the core unit to construct two acceptors BTz-4F-1 and BTz-4Cl-1. 90 When paired with J71, BTz-4F-1 and BTz-4Cl-1 based devices provided PCEs of 5.72% and 3.93%, respectively. Besides the 4T backbone, A3T-2 and A3T-5 with the terthiophene backbone were also designed and provided moderate PCEs of 6.20% and 7.03%, respectively.…”
Section: Nfas With Fully Non Fused Backbonesmentioning
confidence: 96%
“…Torsion angles between them are approximately zero which suggests that methylation of the central bithiazole has insignificant impact on planarity of designed molecules. Both methylated small molecule acceptors (SMAs) exhibit good planarity and a strong intermolecular p‐p stacking effect, which makes charge transfer easier 45 . The core bithiazole and (Z)‐2‐(5,6‐dichloro‐2‐ethylidene‐7‐methyl‐3‐oxo‐2,3‐dihydro‐1 H ‐inden‐1‐ylidene)malononitrile serve as electron acceptor moieties.…”
Section: Resultsmentioning
confidence: 99%
“…Both methylated small molecule acceptors (SMAs) exhibit good planarity and a strong intermolecular p-p stacking effect, which makes charge transfer easier. 45 The core bithiazole and (Z)-2-(5,6-dichloro-2-ethylidene-7-methyl-3-oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile serve as electron acceptor moieties.…”
Section: Computational Detailmentioning
confidence: 99%
“…Besides, Zhu et al synthesized BTz-4F-1 and BTz-4Cl-1, in which halogenated cyanoindanone was used as a strong A terminal. 87 For comparison, an analogue BTz-4F-0 with 2,20-bithiazole was also synthesized. It was found that both NFRAs with dimethylbithiazole exhibited a significantly increasing solubility compared with that of BTz-4F-0.…”
Section: Introductionmentioning
confidence: 99%
“…When a wide bandgap polymer PBFTZ was used as a donor, the Ph-IC-based device showed a PCE of 5.68%. Besides, Zhu et al synthesized BTz-4F-1 and BTz-4Cl-1, in which halogenated cyanoindanone was used as a strong A terminal . For comparison, an analogue BTz-4F-0 with 2,20-bithiazole was also synthesized.…”
mentioning
confidence: 99%